Analysis of the corneal endothelium in eyes of chickens using contact specular microscopy - Luciane de Albuquerque (Semina: Ciências Agrárias, 2015)
The corneal endothelium is a single layer of polygonal cells essential for corneal transparency. The objective of this study was to assess the parameters corneal endothelial cells in healthy chickens of different ages using a contact specular microscopy. A total 36 eyes of 18 chickens were evaluated in this study. After the humane slaughter of birds and subconjunctival enucleation, the eye bulbs were arranged into three groups according to the age of the chickens. Group 1 consisted of bulbs eyes of 6 chickens with ages ranging from 1 to 3 months old. Group 2 consisted of ocular bulbs 6 chickens with ages ranging from 5 to 12 months old. Group 3 consisted of bulbs eyes of 6 chickens with ages ranging from 24 to 40 months old. The contact specular microscopy was easy to perform and provided data such as endothelial cell density, average cell area and cellular pleomorphism. The results obtained with a contact specular microscopy revealed that the aging causes a decrease in the density of the corneal endothelium healthy chickens. Similarly, increasing the average endothelial cell area as well as the pleomorphism occurs. The present work suggests that the parameters of corneal endothelium of healthy chickens present change with advancing age.